2020
DOI: 10.1021/acsabm.0c00763
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sustained Release of Bactericides from Complex Coacervates

Abstract: Materials for preventing harmful bacterial contamination attract widespread interest in areas that include healthcare, home/personal care products, and crop protection. One approach to achieving this functionality is through the sustained release of antibacterial compounds. To this end, we show how putty-like complex coacervates, formed through the association of poly­(allylamine hydrochloride) (PAH) with pentavalent tripolyphosphate (TPP) ions, can provide a sustained antibacterial effect by slowly releasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…This swelling caused the coacervate weight to monotonically increase with time and the coacervate pellets to increase in size and become wispy (see Figure 3 bi). Such a response to deionized water was qualitatively consistent with that seen for polyanion/polycation coacervates (complexes of oppositely charged polyelectrolytes) in deionized water [ 32 , 33 ], and bactericide-loaded PAH/TPP coacervates in tap water [ 21 , 27 ], and—together with the continued slow release from these coacervates in Figure 2 —suggested that the swollen coacervates were composed of water-rich pores dispersed in a continuous coacervate phase. These pores were likely gradually generated due to (1) the high osmotic pressure created by the encapsulated RhB and (possibly) unassociated PAH and TPP, and (2) the greater permeability of the (much smaller) water molecules through the coacervate phase, which allowed the water from the release medium to fill these pores.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…This swelling caused the coacervate weight to monotonically increase with time and the coacervate pellets to increase in size and become wispy (see Figure 3 bi). Such a response to deionized water was qualitatively consistent with that seen for polyanion/polycation coacervates (complexes of oppositely charged polyelectrolytes) in deionized water [ 32 , 33 ], and bactericide-loaded PAH/TPP coacervates in tap water [ 21 , 27 ], and—together with the continued slow release from these coacervates in Figure 2 —suggested that the swollen coacervates were composed of water-rich pores dispersed in a continuous coacervate phase. These pores were likely gradually generated due to (1) the high osmotic pressure created by the encapsulated RhB and (possibly) unassociated PAH and TPP, and (2) the greater permeability of the (much smaller) water molecules through the coacervate phase, which allowed the water from the release medium to fill these pores.…”
Section: Resultssupporting
confidence: 72%
“…The colloid-rich coacervate phase typically has viscoelastic fluid- or gel-like properties [ 4 , 5 , 6 ], and offers numerous benefits: easy formation under mild, aqueous conditions [ 7 , 8 ]; low toxicity [ 9 , 10 ]; and an ability to form, transform their properties, and dissolve in response to external stimuli [ 1 , 11 , 12 , 13 ]. Among their many potential applications (which range from drug delivery [ 8 , 14 , 15 ] to separation processes [ 16 , 17 ], foods [ 18 ], and adhesives [ 11 , 19 , 20 ]), complex coacervates are frequently used in the controlled release of various active compounds [ 8 , 14 , 15 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although its use in medicine is more recent, it has been widely applied in the food industry and for personal care since the early 20th century [ 22 , 23 , 24 ]. The advantages of using a complex coacervate as a controlled release system are significant [ 21 , 25 ]. For example, it provides in situ formation in the aqueous environment without a toxic solvent and shear thinning property, making it suitable for injection.…”
Section: Introductionmentioning
confidence: 99%